Pemantauan Kualitas Air Sekitar Kolam Limbah PPGN Secara Kimia dan Radioaktivitas - Wismawati, Titi; Widarti, Sri; Deddi, Eep; Nugroho, Andung (EKSPLORIUM, 2011)
This research purpose is to monitor the water quality of soil around the waste pond through measurement of chemical constituents (Ca, Mg, Fe, Ni, Zn, Cu, Pb, Mn and U) and water radioactivity. The water quality around tailing pond can be identified by analized the water sample from 4 control wells as deep as 20 m located on the fourth side of the pool and 2 comparison wells with a distance of 50 m and 100 m from the tailing pond. The measurement of chemical constituents of controll well water and comparison well water was done by using Atomic Absorption Spectrophotometer (AAS). The measurement of Uranium content was done by using UV – VIS Spectrophotometer, whereas measurement of radioactivity was measured by Eberline SPA-1 α detector associated with a counter scalers Ludlum model 1000. Determination of the quality of well water was used Storet method. Measurement result obtained in 2010 : the chemical content water in the control wells; Ca (2.31 – 2.91) mg/l, Mg (0.22 – 0.34) mg/l, Fe (0.024 – 0.033) mg/l, Ni (0.0028 – 0.030) mg/l, Zn (0.0019 – 0.025) mg/l, Cu (0.038 – 0.060) mg/l, Pb (0.003 – 0.041) mg/l, Mn (0.004 – 0.005) mg/l, U (0.051 – 0.298) mg/l, Ni (0.003 – 0.004) mg/l, Zn (0.03 – 0.04) mg/l, Cu (0.004 – 0.004) mg/l, Pb (0.003 - 0.003), Mn (0.005 – 0.021) mg/l, and radioactivity of Uranium was (0.025. 10-3 – 0.028.10-3) Bq/l. The radioactivity of control wells in the first quarter (2.321 – 2.635) . 10-2 Bq/l, second quarter (2.162 – 2.823) . 10-2 Bq/l, third quarter (2.424 – 2.931).10-2 Bq/l, fourth quarter (2.283 – 2.643).10-2 Bq/l. The radioactivity of comparison well water in the firs quarter was (2.931 - 2.931). 10-2 Bq/l., second quarter (2.162 – 2.550).10-2 Bq/l, third quarter (2.931- 2.931).10-2, fourth quarter (2.450 – 2.632).10-2 Bq/l. This result showed that there are no pollutant release into the environment. Based on the evaluation result using Storet and US-EPA (Environmental Protection Agency) method, water quality around tailing pond of PPGN – BATAN is expressed as A in class classification (best).